THE RELATIONSHIPS OF WEDDING AGES WITH MOTHER ANXIETY LEVELS PRIMIPARA CONCERNING IN CARING FOR BABIES AGED 0-12 MONTHS IN PUSKESMAS CIOMAS BOGOR DISTRICT, 2018: HUBUNGAN USIA PERNIKAHAN DENGAN TINGKAT KECEMASAN IBU NIFAS PRIMIPARA DALAM MERAWAT BAYI USIA 0-12 BULAN DI PUSKESMAS CIOMAS KABUPATEN BOGOR TAHUN 2018 - Elpinaria Elpinaria Girsang; Salsalina Salsalina Yuniarty; Rizka Rizka Sulistianingsih (Wijaya Husada, 2019)
Based on figures for the incidence of anxiety level in Asia is quite high and very varied between 26-85%, while in Indonesia the incidence rate of anxiety is between 50-70% of postpartum women. In West Java the level of anxiety in primiparous mothers reaches 46%. In Bogor the incidence of anxiety levels is 40-45%. Knowing the age of marriage relations with the mother’s anxiety level parturition primipara in caring for infants aged 0-12 months in Clinics Ciomas Bogor Regency Year 2018. Type of this research is quantitative descriptive with cross sectional designl. This research was conducted in Clinics Ciomas Bogor District the Year 2018 in December 2018 with sample i.e. the mother of primipara who have babies (ages 0-12) as many as 42 people,using the technique of sampling accidental sampling, the instruments used i.e. use the questionnaire the dependent variable on the marriage age and the level of anxiety of maternal childnirth primipara in caring for infants aged 0-12 months on independent variables Whilethe data analysis and statistical testwith bivariat sperman rank. On statistical test of research on the relationship of marriage with the mother’s anxiety level parturition primipara in caring infants aged 0-12 month in Clinics Ciomas Bogor Regency in marriage age i.e. get result there 29 (69%) mothers are not at high risk and 13 (31%) were at high risk. Mother’s anxiety level parturition primipara in caring for a baby there are 19 (45,2%) mothers with mild anxiety and 5 (11,9%) mothers with severe anxiety.The relationship of the age of marriage with the mother’s level of anxiety how can primiparan in caring for a baby there are 16 (55,2%) the respondent suffered a mild anxiety with age nit at risk, 0 (0%) the respondents suffered no anxiety with age at risk. Based on the statistical test sperman shows P Value 0.00 <0.05. So it can be concluded that the Ha accepted Ho denied and it shows no relationshipto age of marriage with the mother’s anxiety level parturition primipara in caring for infants aged 0-12 months in Clinics Ciomas Bogor Regency Year 2018.. The age of the mother influences the level of anxiety of maternal childbirth primipara in caring for infants aged 0-12 months in Clinics Ciomas Bogor Regency 2018, the more risky marriage mother getting heavy levels of anxiety of the mother of the baby in the care of primipara childbith aged 0-12 months in Clinics Ciomas Bogor Regency 2018.